2020
DOI: 10.1371/journal.pone.0240411
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of tobacco cessation including a prescription approach among patients in Swedish primary health care with a focus on socioeconomically disadvantaged areas

Abstract: Background Tobacco Cessation on Prescription (TCP) is a new intervention that is being evaluated in socioeconomically disadvantaged areas in Swedish primary health care (PHC). Patients' perceptions of TCP are important to understand as this may have implications for the acceptability and adherence to treatment and explain cessation outcomes. Patients' general experiences of tobacco cessation are also important to explore to improve cessation support in this setting. Aim To explore experiences of tobacco cessat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Thirteen studies were identified from the search as being fully eligible for inclusion (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) after the initial database search identified 4931 publications (Figure 1). The main reasons for excluding publications were that the article; i) did not describe an appropriate behavior change tool or ii) did not involve a family doctor.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen studies were identified from the search as being fully eligible for inclusion (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) after the initial database search identified 4931 publications (Figure 1). The main reasons for excluding publications were that the article; i) did not describe an appropriate behavior change tool or ii) did not involve a family doctor.…”
Section: Resultsmentioning
confidence: 99%
“…Study designs included quantitative randomised controlled trials (24-28) (n=5), non-randomised experimental (30-32) (n=3), mixed methods (29,33,34) (24-27, 29, 32, 34) and other intervention groups (27,28). Pre/post studies used within-group baseline measures as a comparator (24,31,34), and three studies had no comparator (30,35,36). Most studies were conducted between 2014 and 2020 (n=10) (24,25,(27)(28)(29)(30)(31)(32)(33)36), and in the United States (n=8) (25, 26, 28-31, 33, 34) and Australia (n=3) (24,27,35) The studies ranged in sample size from n=8 (36) to n=520 (29).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations